Back Cover: Deep Learning‐Enhanced Nanopore Sensing of Single‐Nanoparticle Translocation Dynamics (Small Methods 7/2021). Issue 7 (14th July 2021) - Tsutsui, Makusu; Takaai, Takayuki; Yokota, Kazumichi; Kawai, Tomoji; Washio, Takashi
Abstract : In article number 2100191, Makusu Tsutsui, Tomoji Kawai, Takashi Washio, and co‐workers demonstrated the use of deep learning in nanopore sensing. Employing convolutional neural networks, ionic current was denoised in a high dimensional feature space that enabled to visualize hidden signals reflecting fast translocation motions of objects in a nanoscale conduit. This deep denoising paves a way for single molecule fingerprinting by ionic current using solid state nanopores.